USM, UL TO EXPAND NEW AREAS OF INTEREST - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
PENANG, 19 January 2017 The ViceChancellor of Universiti Sains Malaysia (USM), Professor Datuk Dr. Asma Ismail said USM will further enhance collaborations with Universite de Lorraine, France and explore and expand new areas of interest.